ISSUES OF IMPLEMENTING THE STANDARD "PRESENTATION OF FINANCIAL STATEMENTS IN COMMERCIAL BANKS" (IAS 1) IN PRACTICE - Ro‘ziyev Elyor Zafar o‘g‘li (American Journals, 2025)
This article examines the issues of presenting financial statements in commercial banks, specifically the implementation of IFRS 1. Using Asakabank as a case study, the paper provides statistical analysis of the theoretical and practical aspects of adapting international accounting standards to the banking system of Uzbekistan.
Keywords: Financial reporting, IFRS, commercial banks, Asakabank, transparency, international standards.